Datura Stramonium Leaf Extract Toxic Effects on Testis in Swiss Albino Mice Mus musculus - Alwirfli, Soad Mohammed (Scientific Journal for Faculty of Science-Sirte University, 2021)
The notorious weed, jimson weed (Datura stramonium L.) is a hallucinogenic plant that is both toxic and medicinal. The presence of tropane alkaloids, which contain a methylation nitrogen atom (N-CH3) and inhibit neurotransmitters in the brain, is thought to be responsible for the plant’s neurotoxicity. Toxic symptoms have been linked to the recreational use of D. stramonium, according to ethnomedicine. This investigation has been designed to examine the toxicity and describe the possible changes in the structural function of vital organs, following the orally intubation of non-lethal doses of D. stramonium leaves crude aqueous extract. Through preliminary trials, crude aqueous extract. Of 200 mg leaves per kilogram body weight was established as a tolerable non-lethal dose. Three doses 0.36, 0.7, and 4 mg/kg were orally weekly, administered to the male mice in a 0.1 ml volume. Acute toxicity studies were accomplished through oral intubation of three dosages in each case. Observation and mortality were reported for 24 .48, 72 hours. Prolonged toxicity was performed through the administration of weekly, single doses oral for 40 days. The observation was made on the mice’s testis weight and histological abnormality of a testis organ.